Investigation of fractured rock beneath a uranium-tailing storage dam through UAV digital photogrammetry and seismic refraction tomography - Guireli Netto, Leonides [UNESP]; Singha, Kamini; Moreira, César Augusto [UNESP]; Gandolfo, Otávio Coaracy Brasil; Albarelli, Daniel Seabra Nogueira Alves (Frontiers, 2023)
Failure events in dams can be associated with processes in the dam body and in the foundation of the structure. If they are properly identified in early stages, corrective actions can take place, leading to a reduction in the risk of collapse and/or rupture of the dam. Most studies on dams are carried out on the body of the dam; however, problems associated with the foundation of the structure can also lead to loss of stability and subsequent ruptures. This study presents an analysis of the advantages and limitations of the use of seismic refraction in hydrogeological studies of fractured aquifers under pressure from large loads, specifically a dam in this case. Seismic refraction data were collected on an outcrop of fractured rock near a uranium storage dam foundation in southeastern Brazil. The results and interpretations were supported by a structural analysis performed through manual strike measurements collected with a Clark compass and an uncrewed aerial vehicle digital photogrammetry survey in an outcrop. The digital photogrammetric survey mapped the spatial distribution and orientation of the geological structures of the rock mass. Although the structural measurements performed through digital photogrammetry presented greater variability than the measurements collected from the compass, the maximum density of the fracture measurements obtained from both methods were similar and were corroborated by the regional and local fracture patterning. The integration of seismic refraction data with geotechnical and geological investigations allowed us to identify the positioning of structural lineaments in the rock mass and zones with a higher degree of rock alteration. The identification of highly fractured zones in the rock mass from such non-invasive investigations could be used to assist in decision making for structural reinforcements in the foundation of the dam to avoid the loss of stability at the foot of the dam from possible leaks or water flows from the reservoir.
Keywords: dam foundation; geophysics; seismic refraction; UAV; uranium